1999
DOI: 10.1063/1.371093
|View full text |Cite
|
Sign up to set email alerts
|

The effects of KrF pulsed laser and thermal annealing on the crystallinity and surface morphology of radiofrequency magnetron sputtered ZnS:Mn thin films deposited on Si

Abstract: Thin films of ZnS:Mn (800 nm) have been deposited by rf magnetron sputtering onto 100 mm diam n-type single-crystal (100) Si wafers. Specifically for use as active layers in thin film electroluminescent devices, the films need a postdeposition annealing treatment to enhance their luminescent properties. Inherent to the later process step are structural modifications of the phosphor layer which form the basis of this study. Both pulsed laser and thermal postannealing techniques have been investigated. Reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…This conclusion was found to be in agreement with the work from Cattel and Cullis 16 who investigated similar films and substrates. According to our previous work, 15 the observed diffraction peaks in Fig. 1͑a͒ are attributed to the ͑111͒ and ͑311͒ reflection planes.…”
Section: A X-ray Diffraction Analysissupporting
confidence: 62%
See 4 more Smart Citations
“…This conclusion was found to be in agreement with the work from Cattel and Cullis 16 who investigated similar films and substrates. According to our previous work, 15 the observed diffraction peaks in Fig. 1͑a͒ are attributed to the ͑111͒ and ͑311͒ reflection planes.…”
Section: A X-ray Diffraction Analysissupporting
confidence: 62%
“…1͑a͒ are reported from our previous work, 15 and have been corrected for a quanta acquisition time of 20 s. In Ref. 15, we observed that the ZnS:Mn films exhibit predominantly the zincblende structure with a preferred ͗111͘ orientation. In Ref.…”
Section: A X-ray Diffraction Analysismentioning
confidence: 91%
See 3 more Smart Citations